Factors affecting executive function performance of Brazilian elderly in the Stroop test - Braga,P.L.G. (2022)
Aging is related to a decrease in physiological abilities, especially cognitive functions. To unravel further evidence of age-related cognitive decline, we analyzed which physical and functional variables are predictors of cognitive performance in a sample of 498 Brazilian elderly (67.26% women). To do so, we used the Stroop test as a tool to evaluate executive functions and the General functional fitness index (GFFI) to evaluate the functional fitness of the participants. A linear regression analysis revealed that female sex (β=-0.097; t=-2.286; P=0.023), younger age (β=0.205; t=4.606; P<0.0001), more years of education (β=-0.280; t=-6.358; P<0.0001), and higher GFFI (β=-0.101; t=-2.347; P<0.02) were predictors of better cognitive performance. Body mass index (kg/m2) and nutritional status (underweight, eutrophic, overweight, or obese) were not predictors of cognitive performance. Interestingly, among the GFFI tasks, muscle strength influenced the test execution time, both in upper and lower limbs (elbow flexion: β=-0.201; t=-4.672; P<0.0001; sit-to-stand: β=-0.125; t=-2.580; P<0.01). Our findings showed that: 1) women performed the Stroop test faster than men; 2) the older the person, the lower was the cognitive performance; 3) the higher the education, the better the test execution time; and 4) higher scores in the GFFI were associated with a better performance in the Stroop test. Therefore, gender, age, education, and functional fitness and capacity were predictors of cognitive performance in the elderly.